A comparative study of fuzzy logic controller and proportional integral controller on buck-boost converter: article / Zuhairi Hashim - Hashim, Zuhairi (2013)
This thesis is presents a comparative study of Fuzzy Logic Controller (FLC) and Proportional Integral Controller (PIC) on Buck- Boost Converter. The objective is to find comparative performance of both controllers on Buck- Boost Converter. The model circuit of Buck- Boost Converter with FLC and PIC has been derived to analyse the effectiveness of the controls methodology. The controls methodology is then verified by numbers of simulations and the advantages good response time in term of shortest rise time, settlingtime, smaller overshoot and less voltage deviations are indicated in comparison FLC with a conventional PIC. Simulation is held in MATLAB- SIMULINK environment.